Digital Storytelling of the Stories of the Prophets for Developing Religious Character in Early Childhood - Yahya Aziz; Idris Afandi (Yayasan Darusssalam Bengkulu, 2026)
This article analyzes digital storytelling based on prophetic narratives as a pedagogical medium for forming religious character in early childhood education. The study responds to the growing presence of Islamic animation and children’s learning platforms, while questioning how religious values can be mediated through digital narratives without reducing prophetic stories to entertainment. Using qualitative library research and digital content analysis, this article examines KABI Educa Studio as a primary digital object and Joe Lambert’s seven steps of digital storytelling as the main analytical framework. The findings show that prophetic digital storytelling contributes to religious character formation when insight, emotion, selected moral moments, visual design, voice, narrative assembly, and sharing practices are aligned with early childhood development. KABI’s content provides accessible entry points for faith learning through animation, short lessons, and child-friendly characters; however, its pedagogical value depends on adult mediation, ethical curation, and follow-up activities. The study argues that digital storytelling should function as a bridge between prophetic values, affective engagement, and embodied religious habits in family and school contexts.